Enhancing tool life of hot isostatically pressed silicon nitride inserts in machining inconel 718 with different susceptors through hybrid microwave post sintering - Ariff, Tasnim Firdaus; Zolkapli, Farah Farhana; Sapuan, Farah; Azhar, Ahmad Zahirani; Bahar, Rubina; Karim, A.N. Mustafizul; Amin, A. K. M. Nurul (International Journal of Engineering Research and Application, 2018)
Hybrid Microwave sintering has become a growing interest for heating and synthesizing ceramic materials due to its capabilities in successfully enhancing densification and improving mechanical and structural properties. Silicon Nitride (Si3N4) based cutting inserts have outstanding properties for machining hard materials such as cast iron, hard steel and nickel based super alloys. This research aims to analyze the effect of different susceptors on the tool life of various Si3N4 inserts (90Si3N4 4Y2O3 2.5MgO 2Al2O3 1.5SiO) that have been synthesized in machining Inconel 718. The Si3N4 inserts have been synthesized by means of Hot Isostatic Pressing (HIP) at 1800°C and followed by Hybrid Microwave (HMW) post-sintering at 200°C for 10 minutes with the aid of three different susceptors; Silicon Carbide (SiC), Graphite (G) and mixture of (SiC + G) powders. Density, hardness, micro structural properties and tool wear were analyzed. HMW post sintering for only 10 minutes using SiC, G and SiC+G susceptors enhanced the density (97-98%TD) and hardness (27-58%) significantly. Finer uniform grains and less porosities were produced particularly for Si3N4 inserts produced by HMW (SiC+G) when compared with HMW (SiC) and HMW (G). Tool life for the Si3N4 inserts were improved by 10-17% HMW(SiC), 20-53 % HMW(G) and 32-88% HMW(SiC+G) for the cutting speeds of 100, 125 and 160 m/min. Hence, the mixture of SiC +G powders as susceptors produced the best outcome for Si3N4 inserts with enhanced densification, hardness, wear resistance, and longer tool life (88% increment at 100 m/min) when compared with the commercial tool (RNGN 6060) in machining Inconel 718.